Influence of canopy condensate film on the performance of solar chimney power plant - Al-Kayeim, H.H. (2019)
Presence of dust and/or condensate film affects the transmissivity of solar radiation through the transparent canopy/cover of solar collectors. This paper presents experimental investigation results of water vapor film condensate on the upper and lower surfaces of the canopy and how it affects solar chimney performance. The experimental measurements were carried out utilizing the solar chimney model, which has a collector of 7.0 m diameter and chimney of 6.5 m height above the collector. After 10 days of measurements and observation, radiation transmittance was considerably reduced from 7:30 a.m. until 10:30 a.m. due to the presence of condensate. Consequently, collector and solar chimney performance were influenced. A 9â10 variation in solar radiation transmittance was found between dry and wet canopy. The condensate film required 2.0â3.0 h to evaporate. During the evaporation time (7:30 a.m. to 10:30 a.m.), the increase in the collector air temperature under wet canopy was 3.0 Â°Câ5.0 Â°C less compared with that under dry canopy. Solar radiation from the sun until 10:30 a.m. was absorbed by the condensate film to evaporate. A delay was observed in the energy conversion processes from solar to thermal to kinetic, thereby delaying power generation. The presence of water condensate film reduced the hydrothermal performance of the solar chimney by two ways: by reducing the transmittance of solar radiation and by absorbing solar radiation from the water vapor particles to evaporate. An auxiliary heat source that supplies heat before sunrise is necessary to evaporate the condensate film and allow the solar chimney to operate early. Â© 2019